PEMETAAN DESTINASI WISATA DI PULAU TERNATE DENGAN SISTEM INFORMASI GEOGRAFIS - Robo, Sarif; Ainun Tangge, Nurul; Aji, Krishna (Jurnal Lingkungan Almuslim, 2023)
Tourism is one sector that can improve the economy of a region. This sector plays an important role in sustaining life in the surrounding communities. Several studies have reported the condition of tourism but not much has been reported in the archipelago. This study aims to determine the distribution of tourist objects in Ternate Island, North Maluku, Indonesia. The method used is through descriptive analysis with a spatial approach in 2023. This research activity is completing the distribution of tourist objects such as natural attractions, historical and cultural attractions and artificial attractions. The map output that has been compiled presents a distribution of 60 tourist objects consisting of 30 natural attractions, 18 historical and cultural attractions, and 12 artificial attractions. In addition, West Ternate District has the highest number of tourist objects with 24 tourist objects and in North Ternate District there are 12 tourist objects